Sociology of Disciplining Soul and Society: An Analysis of al-Ghazali’s Ontological and Sociological Approaches of Self and Social Accountability - Mohd Shafiq Sahimi; Nordin, Shah Rul Anuar; Sajad Ahmad (Journal of Techno-Social, 2026)
This study examines al-Ghazali’s ontological and sociological frameworks for disciplining the soul and society through Muhasabah al-Nafs (self-accountability) and ‘Amr bi al-Ma’ruf wa Nahyu ‘an al-Munkar (enjoining good and forbidding evil). Drawing from his seminal works, including Ihya’ ‘Ulum al-Din, the research explores how al-Ghazali bridges individual spiritual refinement with collective social responsibility, offering a comprehensive approach to holistic governance in both personal and social domains. The research methodology adopted by the researchers is that of qualitative in nature. It will also employ the textual analysis method to explain the position of the said author and his understanding of the concept. The finding reveals that Muhasabah al-Nafs serves as an introspective mechanism for self regulation, emphasizing continuous self evaluation. It is not possible to realize a good human resource and an ideal social structure by abdicating the disciplinary models set by Islam. Al-Ghazali’s model posits that disciplined individuals form the foundation of a just society as internalized accountability fosters external righteousness. Besides, he has developed a six pronged method of self-discipline and accountability. The present work will focus on how to ensure personality development of an individual through al-Ghazali’s ontological framework of Muhasabah al-Nafs or self introspection. Sociologically, ‘Amr bi al-Ma’ruf functions as a communal duty, ensuring moral coherence through proactive engagement, social criticism and institutional reform. Al-Ghazali balances persuasion and authority, advocating for wisdom (hikmah) and compassion in societal correction. By integrating textual analysis with sociological theory, this paper highlights the relevance of al-Ghazali’s paradigms in contemporary discussions on individual and social responsibility, social activism and holistic leadership. It argues that his dual emphasis on self purification and social reform provides a sustainable model for addressing modern social crises, from individual alienation to collective injustice. The study concludes that al-Ghazali’s synthesis of spiritual discipline and social accountability remains a vital framework for fostering virtuous individuals and harmonious societies. The outcome of the study is to provide a pragmatic roadmap for individual and social upliftment of Muslim Ummah in the light of al-Ghazali’s ontological and sociological framework.